KANDUNGAN GIZI, DAYA CERNA PATI IN VITRO, DAN PENERIMAAN FORMULASI COOKIES BERBASIS TEPUNG PISANG BATU (Musa balbisiana Colla) DENGAN MODIFIKASI ENZIMATIK [NUTRITIONAL COMPOSITION, IN VITRO STARCH DIGESTIBILITY, AND FORMULATION ACCEPTANCE OF COOKIES BASE - Magfhira Tiara Adilla; Ahmad Syauqy; Diana Nur Afifah (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2020)
ABSTRACT In this study, the nutritional composition, in vitro starch digestibility, and formulation acceptance of batu banana flour with enzymatic modification cookies were analyzed. Batu banana (Musa balbisiana Colla) contain high resistant starch that can potentially prevent colorectal cancer. Experimental study with 9 groups of sample tested by duplo, namely non-modified batu banana(Tp1), autoclaving-cooling(TP2), enzymatic autoclaving-cooling(Tp3), enzymatic autoclaving-cooling with autoclaving-cooling(Tp4), and wheat flour(Tp5). The substitutions of Tp1, Tp2, Tp3, and Tp4 were 20%(A) and 40%(B), while Tp5 was 0%(C). The carbohydrate, fat, protein, water, ash, dietary fiber, calcium, and starch digestibility were determined using by different analysis, Soxhlet, the Kjeldahl, oven, drying ash, enzymatic gravimetric, Atomic Absorption Spectrophotometry (AAS), and by in vitro method. Furthermore, organoleptic analysis were determined using hedonic test, while the best formulation using de Garmo method. The results of nutritional composition, starch digestibility content, and acceptance test were analyzed by using Kruskal Wallis and One Way ANOVA. The lowest water median and starch digestibility content mean were Tp4-A (2.81% and 24,22%). The lowest ash content mean was Tp5-C (1.41%). The highest carbohydrate content mean was Tp1-B (60.54%). The highest protein content median was Tp4-A (5.64%).The lowest fat content median was Tp4-B (25.20%). The highest dietary fiber content mean was Tp5-C (4.80%). The highest calcium content mean were Tp3-A and Tp 4-A(1.12%). The acceptance test results were preferred on the color, texture, and taste of Tp5-C, while the aroma for Tp2-A. The most suitable cookies formulation is Tp3-A. ABSTRAK Penelitian dilakukan untuk menganilis kandungan gizi, daya cerna pati in vitro, dan tingkat penerimaan cookies tepung pisang batu dengan metode enzimatik. Pisang batu (Musa balbisiana Colla) mengandung tinggi pati resisten sehingga dapat mengecah kanker kolorektal. Penelitian eksperimental 9 kelompok sampel diuji duplo, yaitu tepung pisang batu non modifikasi (Tp1), autoclaving-cooling (Tp2), autoclaving-cooling enzimatik (Tp3), autoclaving-cooling enzimatik dengan autoclaving-cooling (Tp4), dan tepung terigu (Tp5). Subtitusi Tp1, Tp2, Tp3, dan Tp4 sebesar 20 persen (A) dan 40 persen (B), Tp5 sebesar 0 persen (C). Analisis kadar karbohidrat, lemak, protein, air, abu, serat pangan, kalsium, dan daya cerna pati menggunakan by different, Soxhlet, metode Kjeldahl, oven, drying ash, enzimatik gravimetri, Atomic Absorption Spektrophotometry (AAS), dan in vitro. Sedangkan analisis organoleptik menggunakan uji hedonik dan penentuan formulasi terbaik menggunakan metode de Garmo. Analisis statistik kandungan gizi, daya cerna pati, dan uji penerimaan dianalisis dengan Kruskal Wallis dan One Way ANOVA. Median kadar air dan rerata daya cerna pati terendah pada Tp4-A (2,81% dan 24,22%). Rerata kadar abu terendah pada Tp5-C (1,41%). Rerata kadar karbohidrat tertinggi pada Tp1-B (60,54%). Median kadar protein tertinggi pada Tp4-A (5,64%). Median kadar lemak terendah pada Tp4-B (25,20%). Rerata kadar serat pangan tertinggi pada Tp5-C (4,80%). Rerata kadar kalsium tertinggi pada Tp 3A dan Tp4-A (1,12%). Hasil uji penerimaan yang lebih disukai dari warna, tekstur, dan rasa cookies adalah Tp5-C, sedangkan aroma Tp2-A. Formulasi cookies terbaik adalah Tp3-A.